2016
DOI: 10.1038/cddis.2016.375
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl-tryptophan attenuates regulatory T cells differentiation due to the inhibition of estrogen-IDO1-MRC2 axis in endometriosis

Abstract: Foxp3+ regulatory T (Treg) cells contribute to the local dysfunctional immune environment in endometriosis, an estrogen-dependent gynecological disease, which affects the function of ectopic endometrial tissue clearance by the immune system. The reason for the high percentage of peritoneal Treg in endometriosis patients is unknown. Here, we show that the proportion of peritoneal Treg cells increases as endometriosis progresses. To determine the probable mechanism, we established a naive T cell-macrophage-endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Many studies have shown that Treg are increased in the peritoneal cavity of endometriosis patients; however, two studies did not find a significant difference . In a mouse study, the inhibition of Treg induction (differentiation) reduced the number and weight of endometriotic lesions . These findings indicate that Treg play a role in endometriosis progress, although further studies are required to discover the mechanism and therapeutic targets.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Many studies have shown that Treg are increased in the peritoneal cavity of endometriosis patients; however, two studies did not find a significant difference . In a mouse study, the inhibition of Treg induction (differentiation) reduced the number and weight of endometriotic lesions . These findings indicate that Treg play a role in endometriosis progress, although further studies are required to discover the mechanism and therapeutic targets.…”
Section: Introductionmentioning
confidence: 91%
“…73,88 In a mouse study, the inhibition of Treg induction (differentiation) reduced the number and weight of endometriotic lesions. 87 These findings indicate that Treg play a role in endometriosis progress, although further studies are required to discover the mechanism and therapeutic targets.…”
Section: Th17 and Treg In Endometriosismentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, PODXL expression was significantly upregulated in these cells, whereas a downregulation was observed in 12Z cells (Figure A,B). As GSI affected the cell viability of our cell models, we evaluated a potential GSI‐induced dysregulation of IDO1 , which has been linked to proliferation, invasive growth, and immunomodulatory potential of endometriotic stroma cells . Although GSI treatment did not significantly affect IDO1 mRNA expression in 12Z cells, a trend for an upregulation ( P = 0.077) was observed in the case of patient‐derived endometriotic stroma cells (Figure A,B).…”
Section: Resultsmentioning
confidence: 97%
“…As GSI affected the cell viability of our cell models, we evaluated a potential GSI-induced dysregulation of IDO1, which has been linked to proliferation, invasive growth, and immunomodulatory potential of endometriotic stroma cells. 18,19 Although GSI treatment did not significantly affect IDO1 mRNA expression in 12Z cells, a trend for an upregulation (P = 0.077) was observed in the case of patient-derived endometriotic stroma cells (Figure 2A,B). In contrast to LIFR, SOX2, and IFITM1, we could not independently confirm a significant regulation of TERT, MNX1, IFITM2, DDX4, FOXA2, Nestin, nanog, WNT1, DES, Lefty, nodal, SOX17, MYOD1, IL6ST, and CGB in 12Z cells (Figure 3).…”
Section: Gsi Affects Expression Of the Stemness-related Factors Heymentioning
confidence: 91%